2018
DOI: 10.1007/s11661-018-4497-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Growth of Austenite from As-Quenched Martensite in Medium Mn Steels

Abstract: As part of an ongoing development of third-generation advanced high-strength steels with acceptable cost, austenite reversion treatment of medium Mn steels becomes attractive because it can give rise to a microstructure of fine mixture of ferrite and austenite, leading to both high strength and large elongation. The growth of austenite during intercritical annealing is crucial for the final properties, primarily because it determines the fraction, composition, and phase stability of austenite. In the present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
4
27
1
Order By: Relevance
“…The austenite reversion rate was predicted to be decelerated due to cementite precipitation. It was also found by Huyan et al [367] that the predicted kinetics of austenite reversion can be in good agreement with experiments if a finite mobility of the martensite/austenite interfaces is assumed in the setup A simulations, e. g. Setup A + M. Zhang et al [323] reported that the kinetics of lath-shaped austenite reversion and alloying elements partitioning behaviour in the low Mn steels can also be well predicted based on Setup O + M, assuming the mobility of martensite/austenite interface is much lower than that of ferrite/austenite interface. It should be noted that the effect of cementite precipitation on the kinetics of austenite reversion was not considered in Setup O + M, although cementite precipitation was observed by Zhang et al [323].…”
Section: Interaction Between Carbide Precipitation-dissolution and Austenite Reversionsupporting
confidence: 70%
See 3 more Smart Citations
“…The austenite reversion rate was predicted to be decelerated due to cementite precipitation. It was also found by Huyan et al [367] that the predicted kinetics of austenite reversion can be in good agreement with experiments if a finite mobility of the martensite/austenite interfaces is assumed in the setup A simulations, e. g. Setup A + M. Zhang et al [323] reported that the kinetics of lath-shaped austenite reversion and alloying elements partitioning behaviour in the low Mn steels can also be well predicted based on Setup O + M, assuming the mobility of martensite/austenite interface is much lower than that of ferrite/austenite interface. It should be noted that the effect of cementite precipitation on the kinetics of austenite reversion was not considered in Setup O + M, although cementite precipitation was observed by Zhang et al [323].…”
Section: Interaction Between Carbide Precipitation-dissolution and Austenite Reversionsupporting
confidence: 70%
“…It should be noted that the effect of cementite precipitation on the kinetics of austenite reversion was not considered in Setup O + M, although cementite precipitation was observed by Zhang et al [323]. This could explain why the mobility of martensite/austenite interface adopted by Zhang et al [323] is smaller than that adopted by Huyan et al [367].…”
Section: Interaction Between Carbide Precipitation-dissolution and Austenite Reversionmentioning
confidence: 95%
See 2 more Smart Citations
“…Each of these elements contributes differently to the stability of the iron-rich solutions (liquid, ferrite, austenite (c), and epsilon (e)) and the second-phase precipitates. [65][66][67][68][69] The purpose of this section is to present a few key concepts relevant to the thermodynamically guided design of AHSS. The intention is not to present a general review about alloy thermodynamics here.…”
Section: A Key Thermodynamic Concepts For Advanced High-strength Stementioning
confidence: 99%